Retirement and Skill Issues in Northern Ontario Industries - LeBrasseur, Rolland (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This study is afollow-up to Schell et al. (1989), and explores the occupational and age profiles of employees 45-64 years old in relation to retirement issues. Three profiles are presented: sociodemographic including health, present and future finances, and retirement age intentions and opinions. Effective retirement packages are discussed as a matching of company and employee interests, and as a tool for managing human resource flows.